Fuel energy transportation and transformation based on the hydrogen obtainment system by solid-oxide fuel-cell and ethanol steam reforming integration - Cordaro, P. G.B. [UNESP]; Gallego, A. G.; Silveira, J. L. [UNESP] (Elsevier, 2025)
In operation, hydrogen transportation can be subjected to frequent issues due to the complexity of its storage containment. This work investigates the transportation of a blend of ethanol and water instead hydrogen (e.g., compressed), combined with the usage of a compacted station (ten feet container volume) operated by a Solid-Oxide Fuel-Cell (SOFC) and an Ethanol-Steam-Reformer (ESR) integrated as a system. This system aims to produce clean-hydrogen and electricity either concomitantly or alternately, directly at the final consumer location (e.g., industrial facilities or refueling stations), establishing it as a valid alternative for energy transportation of fuel, particularly addressing the complexity of hydrogen transportation. A previous energy-mass balance studied related to hydrogen/electricity obtainment, based on exactly this stationary compacted station design, is used. An exergetic analysis related to the operation of the system (SOFC and ESR combined) complements the previous study based only on energy and mass balance. The investigation focused on a simulation of 1 kg of hydrogen production, involving the addition of an electrolysis (ELE) rig. The simulations conducted demonstrated operationally optimized values for ESR temperatures. It noticed a system exergetic efficiency of 79.8 % for an ESR temperature of 660 K (387 °C). Additionally, a methodology based on Value-Analysis (VA) or Value-Engineering (VE) is applied to evaluate the ethanol–water blend's carrying features compared to compressed hydrogen transport. The value of the function ‘retain the volume/mass’ of the ethanol–water blend is 31.4 % enhanced, compared to the hydrogen gas compressed, which is precisely the main disadvantage of hydrogen carrying.
Keywords: Clean Hydrogen obtainment; Energy transportation; Exergetic analysis; Value analysis